Kerja Sama Guru PAI dengan Orang Tua dalam Membina Akhlak Siswa pada Generasi Alpha di Sekolah Menengah Pertama - Fadhilah, Atikah; Mardianto, Mardianto (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
This research aims to build student morality in the Alpha generation through PAI teacher cooperation with parents in building a student mentality in the Alpha generation in the Field Pahlawan Nasional. A picture of student morals and the efforts made by PAI teachers with parents to overcome the difficulties faced in building students' morals in the Alpha generation is presented in the Field Pahlawan Nasional SMP. The research method used is a qualitative one with a case study approach through observation and interview. The results of this study showed that the ethics of students in the Pahlawan Nasional School are already in accordance with the commands of God SWT. This is demonstrated by the way students interact using a language that is polite to older people as well as to peers, and are accustomed to greeting and welcoming when meeting with teachers. Students’ parents also consult directly with PAI teachers via phone and direct visits to the school to learn about their child’s moral and mental development at school. Parents should know their child’s community in the surrounding area; PAI teachers teach Islamic Religious Education, especially about building ethics in this Alpha generation; parents should also improve their Islamic education so that their children can take the example of their parents.